Dietary long-chain polyunsaturated fatty acids upregulate expression of FADS3 transcripts - Reardon, Holly T. (2012)
The fatty acid desaturase (FADS) gene family at 11q12-13.1 includes FADS1 and FADS2, both known to mediate biosynthesis of omega-3 and omega-6 long-chain polyunsaturated fatty acids (LCPUFA). FADS3 is a putative desaturase due to its sequence similarity with FADS1 and FADS2, but its function is unknown. We have previously described 7 FADS3 alternative transcripts (AT) and 1 FADS2 AT conserved across multiple species. This study examined the effect of dietary LCPUFA levels on liver FADS gene expression in vivo and in vitro, evaluated by qRT-PCR. Fourteen baboon neonates were randomized to three diet groups for their first 12 weeks of life: C: Control, no LCPUFA; L: 0.33% docosahexaenoic acid (DHA)/ 0.67% arachidonic acid (ARA) (w/w); and L3: 1.00% DHA/ 0.67% ARA (w/w). Liver FADS1 and both FADS2 transcripts were downregulated by at least 50% in the L3 group compared to controls. In contrast, FADS3 AT were upregulated (L3>C), with four transcripts significantly upregulated by 40% or more. However, there was no evidence for a shift in liver fatty acids to coincide with increased FADS3 expression. Significant upregulation of FADS3 AT was also observed in human liver-derived HepG2 cells after DHA or ARA treatment. The PPARγ antagonist GW9662 prevented FADS3 upregulation, while downregulation of FADS1 and FADS2 was unaffected. Thus, FADS3 AT were directly upregulated by LCPUFA by a PPARγ-dependent mechanism unrelated to regulation of other desaturases. This opposing pattern and mechanism of regulation suggests a dissimilar function for FADS3 AT compared to other FADS gene products.